ISOLATION AND CHARACTERIZATION OF ENDOPHYTIC BACTERIA IN SEVERAL FORAGE GRASS CULTIVARS - Hà, Nguyễn Thị Thu (Vietnam Journal of Biotechnology, 2011)
Four    wild   forage   grass  cultivars  (Pennisetum purpureum,         Pannicum     maximum,   Brachiaria mutica,  Ischaemum rugosum) were  collected   in three provinces   (Vinh   Long,  Dong  Thap,  Can   Tho)  of the  Mekong Delta, Vietnam to isolate, identify, evaluate some good characteritics of these endophytes, determine nifH gene   in   nifrogen-fixing   endophytes   and   sequence   some   good   endophytes.   The   results   showed   that   seventy-one bacterial   isolates   were   isolated   in   several   forage  grass   cultivars.   However,   42   isolates   were   identified  as endophytic     bacteria  using   16S   rDNA     analysis  with   specific  primers.   Thirteen    endophytes    with  a  good composite characteristics  (high lAA biosynthesis, phosphate solubilization   and fixing nifrogen)   were detected based   on   biochemical   tests.  Among   them,   7   endophytes   in   Nfb   medium     were   identified  as Azospirillum    lipoferum. Furthermore,   G4   and   G6   endophytes isolated  in   LGI   medium,   they  showed   93.8   and  94.3% identities   with   Klebsiella pneumoniae about   nifA   gene   and   the   identity   of   nifH   gene  from   H4   endophytic bacteria with in Micrococcus sp. Y70 was 97.5%. Three endophytes (A18, G4 and H4) had the best composite characteristic, they have been suggested for bio-fertilizer production.